Automated Diabetic Retinopathy Screening in Out-patient Diabetes Care – Comparison of Two Artificial Intelligence Algorithms: RetCAD and OphtAI - Bauer, Florian Maria; Sauerbeck, Annette; Hitzl, Wolfgang; Piravej, Nick; Schmidbauer, Josef (Klinische Monatsblätter für Augenheilkunde, 2025)
Objective The artificial intelligence (AI) can be applied to screening for diabetic retinopathy (DR) from colour fundus photographs. The prerequisite for this is that the AI used can achieve a similar performance in the real world in different study conditions. The aim of this study is therefore to test and compare the latest version of the AI-based algorithms RetCAD and OphtAI for DR screening in a diabetes outpatient clinic.Methods In the period from August 2023 to November 2023, 150 diabetics were recruited at the outpatient diabetes center of the University Hospital. For each study participant, images were taken with the handheld retinal camera Aurora (Optomed Plc, Oulu, Finland) in Miosis. The images were examined by the ophthalmologist and by the AI-based algorithms RetCAD version 2.2.0 (Thirona Retina, Nijmegen, Netherlands) and OphtAI version 2.3.4 (Groupe Evolucare Technologies, Le Pecq, France) for the presence of DR. The severity of DR was classified using the International Clinical Diabetic Retinopathy (ICDR) scale. Patients with no retinal changes or a mild DR were advised to have an ophthalmological check-up in one year. In the presence of a moderate, severe or proliferative DR, a referral to the treating ophthalmologist was made. For this reason, the severity levels of moderate, severe and proliferative DR have been summarised under the umbrella term of referable DR.Results No DR was detected in 123 out of 143 (86.0%) diabetics and mild DR was detected in 10 (7.3%). All patients with moderate DR 7 (5.0%), severe 2 (1.5%) and proliferative DR 1 (0.7%) were grouped together as refererable DR and represented a proportion of 7.3%. The AI-based algorithm RetCAD version 2.2.0 achieved a sensitivity of 90% and a specificity of 100% for the detection of a referable DR compared to ophthalmological image assessment. RetCAD rated 98% of the images for image analysis as sufficient or better. In contrast, the second AI-based algorithm OphtAI version 2.3.4 achieved a sensitivity of 70% and a specificity of 100% for the detection of a referable DR. The OphtAI software was able to perform image analysis on all images.Conclusion The results for the detection of a referable DR were consistent under study conditions and in clinical use for the AI-based algorithm RetCAD. The AI-based algorithm OphtAI, on the other hand, detected fewer patients with moderate DR, which was reflected in lower sensitivity. Both algorithms correctly assigned all patients with severe and proliferative DR. The AI-based algorithms RetCAD and OphtAI tested appear to be suitable for use in a diabetes outpatient clinic and primary care setting, respectively.Hintergrund Der Einsatz von künstlicher Intelligenz (KI) bietet sich für die Früherkennung der diabetischen Retinopathie (DR) anhand von Netzhautbildern an. Voraussetzung ist, dass die eingesetzte KI, die unter Studienbedingungen erzielte Performance auch unter Real-World-Gegebenheiten erreicht. Ziel dieser Studie ist es, die auf KI-basierenden Algorithmen RetCAD und OphtAI in der aktuellsten Version für die Vorsorgeuntersuchung auf DR in einer diabetologischen Ambulanz zu testen.Patienten und Methoden Im Zeitraum von August bis November 2023 wurden 150 Personen mit Diabetes im ambulanten Behandlungszentrum der Diabetologie am Universitätsklinikum rekrutiert. Bei jedem Studienteilnehmer wurden Fundusbilder mit der mobilen Kamera Aurora (Optomed Plc, Oulu, Finnland) in Miosis aufgenommen. Die Aufnahmen wurden vom Augenarzt und von den auf KI basierenden Algorithmen RetCAD Version 2.2.0 (Thirona Retina, Nijmegen, Niederlande) und OphtAI Version 2.3.4 (Groupe Evolucare Technologies, Le Pecq, Frankreich) auf das Vorliegen einer DR untersucht. Der Schweregrad der DR wurde anhand der internationalen Klassifikation eingeteilt. Personen mit Diabetes ohne DR oder einer milden DR wurde eine augenärztliche Kontrolle in einem Jahr empfohlen. Bei Vorliegen einer moderaten, schweren oder proliferativen DR erfolgte eine Überweisung an den behandelnden Augenarzt.Ergebnisse Bei 123 von 143 (86,0%) Personen mit Diabetes wurde keine DR und bei 10 (7,3%) eine milde DR erkannt. Alle Patienten mit einer moderaten DR 7 (5,0%), einer schweren 2 (1,5%) und einer proliferativen DR 1 (0,7%) wurden als überweisungsbedürftige DR zusammengefasst und stellten einen Anteil von 7,3% dar. Der auf KI basierende Algorithmus RetCAD Version 2.2.0 erreichte eine Sensitivität von 90% und eine Spezifität von 100% für die Erkennung einer überweisungsbedürftigen DR im Vergleich zur augenärztlichen Bildbeurteilung. RetCAD bewertete 98% der Bilder für die Bildanalyse als ausreichend oder besser. Der zweite KI-basierte Algorithmus OphtAI Version 2.3.4 erzielte eine Sensitivität von 70% und eine Spezifität von 100% für die Detektion einer überweisungsbedürftigen DR. Eine Bildanalyse konnte bei allen Aufnahmen durchgeführt werden.Schlussfolgerung RetCAD erreichte im klinischen Einsatz für das Erkennen einer überweisungsbedürftigen DR die unter Studienbedingungen angegebene Performance. Der zweite Algorithmus OphtAI erkannte weniger Patienten mit moderater DR, was sich in einer geringeren Sensitivität widerspiegelte. Von beiden Algorithmen wurden alle Patienten mit schwerer und proliferativer DR richtig zugeordnet. Die getesteten KI-basierten Algorithmen RetCAD und OphtAI scheinen für den Einsatz in einer Diabetesambulanz beziehungsweise in der Primärversorgung geeignet.
Keywords: artifical intelligence; RetCAD; OphtAI; diabetic retinopathy; screening; Aurora